Taxonomy, evolution, and biostratigraphy of conodonts from the Kechika Formation, Skoki Formation, and Road River Group (Upper Cambrian to Lower Silurian), Northeastern British Columbia - Pyle, Leanne J.; Barnes, Christopher R. (NRC monograph publishing program., 2002)
Conodonts, the tiny, phosphatic, tooth-like remains of an extinct group of early vertebrates, are the most important fossil group for biostratigraphy throughout their stratigraphic range from Late Cambrian to Late Triassic. This monograph represents a benchmark study of these important zonal fossils. The detailed paleontological work not only provides a taxonomic basis for future studies on early Paleozoic conodonts but also focuses on the evolution of conodonts in the early Ordovician, a time of extraordinary adaptive radiation. The taxonomic work provides detailed descriptions and illustrations of 185 species representing 69 genera. Seven new genera and 39 new species are described. The high diversity of taxa across the platform-to-basin transect shows the biogeographic differentiation and spatial ecological partitioning of conodonts through time. The taxonomy permits the refinement to the biostratigraphic zonation within two faunal realms for British Columbia that can be correlated with schemes elsewhere in North America and also internationally.